Step 1

To solve the equation

Step 2

given equation is 5x−4=2(x−2)

5x-4=2x-4

5x-2x=-4+4

3x=0

x=0

To solve the equation

Step 2

given equation is 5x−4=2(x−2)

5x-4=2x-4

5x-2x=-4+4

3x=0

x=0

jackbranv5

Answered 2021-11-22
Author has **171** answers

breisgaoyz

Answered 2021-11-23
Author has **417** answers

Step 1: Write the data as a generalized function

5x-4=2(x-2)

5x-4=2x-4

Step 2: Add 4 to both parts of the equation

5x-4+4=2x-4+4

Step 3: Simplification

5x=2x-4+4

5x=2x

Step 4: Subtract 2x from both parts of the equation

5x-2x=2x-2x

Step 5: Simplification

3x=2x-2x

3x=0

Step 6: Divide both parts of the equation by one term

\(\displaystyle{\frac{{{3}{x}}}{{{3}}}}={\frac{{{0}}}{{{3}}}}\)

Step 7: Simplification

\(\displaystyle{x}={\frac{{{0}}}{{{3}}}}\)

The solution

x=0

5x-4=2(x-2)

5x-4=2x-4

Step 2: Add 4 to both parts of the equation

5x-4+4=2x-4+4

Step 3: Simplification

5x=2x-4+4

5x=2x

Step 4: Subtract 2x from both parts of the equation

5x-2x=2x-2x

Step 5: Simplification

3x=2x-2x

3x=0

Step 6: Divide both parts of the equation by one term

\(\displaystyle{\frac{{{3}{x}}}{{{3}}}}={\frac{{{0}}}{{{3}}}}\)

Step 7: Simplification

\(\displaystyle{x}={\frac{{{0}}}{{{3}}}}\)

The solution

x=0

asked 2021-09-30

Solve the equation.

\(\displaystyle{\frac{{{4}}}{{{x}+{2}}}}+{\frac{{{1}}}{{{x}-{2}}}}={\frac{{{5}{x}-{6}}}{{{x}^{{{2}}}-{4}}}}\)

\(\displaystyle{\frac{{{4}}}{{{x}+{2}}}}+{\frac{{{1}}}{{{x}-{2}}}}={\frac{{{5}{x}-{6}}}{{{x}^{{{2}}}-{4}}}}\)

asked 2021-09-12

Solve the equation 6x - 3(5x + 2) = 4(1 - x), inequality, or system of equations.

asked 2021-09-19

Solve the equation.

\(\displaystyle{\frac{{{4}}}{{{5}{x}+{2}}}}-{\frac{{{12}}}{{{15}{x}+{6}}}}={0}\)

\(\displaystyle{\frac{{{4}}}{{{5}{x}+{2}}}}-{\frac{{{12}}}{{{15}{x}+{6}}}}={0}\)

asked 2021-11-20

Solve the equation.

\(\displaystyle{\frac{{{3}+{5}{x}}}{{{5}}}}={\frac{{{4}-{x}}}{{{7}}}}\)

\(\displaystyle{\frac{{{3}+{5}{x}}}{{{5}}}}={\frac{{{4}-{x}}}{{{7}}}}\)

asked 2021-11-19

Solve the equation.

1.5x-0.7=0.4(3-5x)

1.5x-0.7=0.4(3-5x)

asked 2021-02-21

Solve the given system of equations by matrix equation.

5x-4y=4

3x-2y=3

5x-4y=4

3x-2y=3

asked 2021-11-20

Solve the equation.

\(\displaystyle{\frac{{{9}}}{{{2}{x}+{6}}}}-{\frac{{{7}}}{{{5}{x}+{15}}}}={\frac{{{2}}}{{{3}}}}\)

\(\displaystyle{\frac{{{9}}}{{{2}{x}+{6}}}}-{\frac{{{7}}}{{{5}{x}+{15}}}}={\frac{{{2}}}{{{3}}}}\)